2018
DOI: 10.1080/21645515.2018.1430543
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination 2014–2015: Results of a survey conducted among general practitioners in Italy

Abstract: Introduction: The aim of the present study was to evaluate orientation, organizational procedures implemented and difficulties faced by general practitioners (GPs) during the 2014/15 seasonal influenza vaccination programme, as well as GPs' general attitude towards vaccinations.Methods: An ad hoc online survey was developed and administered to general practitioners members of the Italian Federation of GPs (Federazione Italiana Medici di Medicina Generale – FIMMG). Overall, 10,000 survey invitations were sent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…A better understanding of the role of HCPs for alleviating asymmetric information among high-risk patients like the elderly, is important for the design of future health policy interventions and increasing vaccination coverage rates [ 42 ]. However, two Italian surveys regarding influenza seasons 2014/15 [ 43 ] and 2017/18 [ 39 ] found that only half of GPs had the possibility of choosing from among the available vaccine types. It has also been suggested [ 39 ] that the availability of explicit guidelines on the appropriateness of the use of individual influenza vaccine types could increase vaccine uptake in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the role of HCPs for alleviating asymmetric information among high-risk patients like the elderly, is important for the design of future health policy interventions and increasing vaccination coverage rates [ 42 ]. However, two Italian surveys regarding influenza seasons 2014/15 [ 43 ] and 2017/18 [ 39 ] found that only half of GPs had the possibility of choosing from among the available vaccine types. It has also been suggested [ 39 ] that the availability of explicit guidelines on the appropriateness of the use of individual influenza vaccine types could increase vaccine uptake in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…The influenza vaccination coverage among primary care (PC) staff was lower than the usual 75% coverage recommended by WHO [ 20 , 21 ]. Nevertheless, it was still higher than most rates found in the health sector around the world [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if vaccine effectiveness is difficult to assess, vaccination is still one of the only proven prevention methods against influenza [ 18 , 19 ], leading to a lower rate of influenza infection in vaccinated HCW [ 9 ]. A study in 2016 showed that the vaccination rate among HCW was highly variable and as low as around 40% in Europe, compared to 77% in USA [ 20 ], while a recent Italian study found a vaccination rate of 30% among primary care physicians [ 21 ]. In Switzerland, that rate was estimated around 16% for the years 2012 and 2017 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the 2018/2019 season seems to show a turnaround, with a growing percentage of people requiring to be vaccinated and a projected increase in vaccination coverage [10]. The increased demand could help improve vaccination coverage, although it remains important to also strengthen the commitment of public health authorities [11] and access to vaccination.…”
mentioning
confidence: 99%